Données préliminaires sur la structure qualitative et quantitative du phytoplancton du lac Sinoe pendant les années 1973 – 1977 - Roban, Anca; Stadniciuc, Maria (Cercetări Marine - Recherches Marines, 2026)
The qualitative and quantitative data on phytoplankton of Sinoe Lake in a five-year period, is summarized. The dominant systematic groups had remained the same throughout the period. The Diatomeans have reached a peak in 1976-77 (54.28% and 53.52% respectively); the Chlorophyceans in 1974 (32.05%) and Cyanophyceans in 1975 (25.00%). Also, in all the years, the freshwater species prevailed, both qualitatively and quantitatively.